The Influence of Human Resource Development and Organizational Communication on Employee Performance in Companies in Cirebon City - Eteh Resa Asyifa; Muhamad Isfan Arqunabil; Obbi Agung Saputra; Ricco Andriansyah Nurjati (Sean Institute, 2026)
This study aims to analyze the influence of human resource development strategies and organizational communication on employee performance in Cirebon City. In an era of increasingly competitive business environment, effective human resource development and organizational communication are crucial factors in improving employee performance. This study was conducted to determine the extent to which these two variables influence employee performance in organizations/companies in Cirebon City. The research method used is a quantitative approach with data collection techniques through questionnaires. The research population was employees at companies/agencies in Cirebon City with a sample of [X] respondents selected using a purposive sampling technique. The research instrument used a Likert scale that has been tested for validity and reliability. The data analysis technique used multiple linear regression analysis with the help of SPSS software.The results of the study indicate that: (1) Human resource development strategies have a positive and significant effect on employee performance in Cirebon City; (2) Organizational communication has a positive and significant effect on employee performance; (3) Simultaneously, human resource development strategies and organizational communication have a significant effect on employee performance with a contribution of [X]%. This study recommends that organizations in Cirebon City improve their human resource development programs and improve organizational communication patterns to optimize employee performance.